Question
upstudy study bank question image url

5. \( 2^{-2 n}\left(2^{n+1}\right)=2^{-2 n} \)

Ask by Ayala Simmons. in the United States
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

\( n = -1 \)

Solution

Solve the equation \( 2^{-2n}(2^{n+1})=2^{-2n} \). Solve the equation by following steps: - step0: Solve for \(n\): \(2^{-2n}\times 2^{n+1}=2^{-2n}\) - step1: Multiply the terms: \(2^{-n+1}=2^{-2n}\) - step2: Set the exponents equal: \(-n+1=-2n\) - step3: Move the variable to the left side: \(-n+1+2n=0\) - step4: Add the terms: \(n+1=0\) - step5: Move the constant to the right side: \(n=0-1\) - step6: Remove 0: \(n=-1\) The solution to the equation \(2^{-2n}(2^{n+1})=2^{-2n}\) is \(n=-1\).

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Bonus Knowledge

To solve the equation \( 2^{-2 n}(2^{n+1})=2^{-2 n} \), start by simplifying the left side. You have \( 2^{-2 n} \cdot 2^{n + 1} \). When multiplying exponents with the same base, you can add the exponents: \[ 2^{-2n + (n + 1)} = 2^{-2n + n + 1} = 2^{-n + 1}. \] So the equation now becomes: \[ 2^{-n + 1} = 2^{-2n}. \] Since the bases are the same, you can set the exponents equal to each other: \[ -n + 1 = -2n. \] Now, isolate \(n\): \[ 1 = -2n + n, \] \[ 1 = -n, \] \[ n = -1. \] Thus, the solution to the equation is \( n = -1 \).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy